Potensi dan Tantangan Artificial Intelligence dalam Pembelajaran di Sekolah Menengah: Systematic Literature Review - Fivediniar Edra Primaulidina; Siti Annisa Safitri; Nurhaliza Meilinda Iswanto (International Forum of Researchers and Lecturers, 2025)
Artificial Intelligence (AI) has brought changes in various sectors including education, particularly at the secondary school level. This study aims to analyze the role of AI in improving academic learning, identify the positive impact of AI implementation in the education sector, and compare the effectiveness of AI-based learning with conventional methods. Using the Systematic Literature Review (SLR) method, this study analyzed 50 scientific articles published between 2019-2024 from ScienceDirect, IEEE, Semantic Scholar, and Google Scholar databases. The results showed that the implementation of AI improved students' academic performance by 23% compared to traditional methods, with an increase in students' learning motivation by 35%. In the aspect of adaptive learning, AI shows an increase in learning effectiveness by 30% and increases student participation in distance learning by 40%. Comparison with conventional methods shows the superiority of AI-based learning in material personalization (90% vs 60%), feedback system (85% vs 40% responsiveness), and student engagement (75% vs 45%). However, the research found that optimal results are achieved through blended learning that combines the power of AI with the social interaction of conventional learning.